2017
DOI: 10.1016/j.celrep.2017.10.118
|View full text |Cite
|
Sign up to set email alerts
|

Quiescence Exit of Tert+ Stem Cells by Wnt/β-Catenin Is Indispensable for Intestinal Regeneration

Abstract: SUMMARY Fine control of stem cell maintenance and activation is crucial for tissue homeostasis and regeneration. However, the mechanism of quiescence exit of Tert+ intestinal stem cells (ISCs) remains unknown. Employing a Tert knock-in (TertTCE/+) mouse model, we found that Tert+ cells are long-term label-retaining self-renewing cells, which are partially distinguished from the previously identified +4 intestinal stem cells (ISCs). Tert+ cells become mitotic upon irradiation (IR) injury. Conditional ablation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 44 publications
6
51
0
Order By: Relevance
“…The identity of this cell in human colonoids is currently 262 unknown but under further investigation. Regeneration following cytotoxin-induced injury 263 results in diffuse WNT2B staining with a higher number of WNT2B+ cells, similar to a study 264 that showed upregulation of Wnt2b in mouse intestinal crypts post-irradiation (Suh et al, 2017).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The identity of this cell in human colonoids is currently 262 unknown but under further investigation. Regeneration following cytotoxin-induced injury 263 results in diffuse WNT2B staining with a higher number of WNT2B+ cells, similar to a study 264 that showed upregulation of Wnt2b in mouse intestinal crypts post-irradiation (Suh et al, 2017).…”
supporting
confidence: 66%
“…These findings highlight the importance of epithelial WNT2B and DHH in 29 regulating human colonic regeneration after injury. 30 31Thus far, only three studies have detailed the importance of epithelial Wnts in 55 homeostasis or response to injury in the intestine (O'Connell et al, 2018;Suh et al, 2017; Zou et 56 al., 2018), with most studies focused on the role of mesenchymal Wnts in homeostasis and 57 disease (Gregorieff et al, 2005;Greicius et al, 2018;Koch, 2017; Shoshkes-Carmel et al, 2018; 58 Valenta et al, 2016). The majority of data gained on mouse intestinal injury models suggests that 59 the mesenchymal Wnts are necessary for epithelial regeneration, but did not characterize the role 60 epithelial Wnts may be playing in these processes.…”
mentioning
confidence: 99%
“…Taken together, these results demonstrate that Erdr1 stimulates in vitro intestinal epithelial wound closure in mouse and human cells. highly sensitive to DNA damage caused by radiation 39 , and the self-renewal capacity of Lgr5 + ISCs is key to recovery 40,41 . Based on our findings that Erdr1 increased the number of Lgr5 + ISCs and promoted TA cell proliferation in the steady state, we explored whether Erdr1 could mediate similar effects in vivo following radiation-induced injury.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer stemness is not a rigid trait but can be modulated by the Wnt signaling pathway, which controls self-renewal and the multi-differentiation capacity of CSCs [21]. It has been suggested that after IR, Wnt helps to regenerate tissue and Wnt5a promotes glioblastoma stem cell differentiation [52][53][54]. The close link between Wnt signaling, cancer stemness, and EMT may be one mechanism underlying Wnt-induced radioresistance.…”
Section: Wnt Signaling Is Associated With Cscs and Emt And Promotes Rmentioning
confidence: 99%